2021
DOI: 10.1021/acscatal.0c05436
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field-Assisted Photoelectrochemical Water Splitting: The Photoelectrodes Have Weaker Nonradiative Recombination of Carrier

Abstract: The manipulation of photoelectrodes' electron− hole pairs toward low recombination is the fundamental strategy to achieve high solar-to-hydrogen conversion efficiency in photoelectrochemical (PEC) water splitting cells. Herein, we demonstrate that a magnet placed parallel to a photoelectrode can improve the water splitting activity of typical BiVO 4 and α-Fe 2 O 3 photoanodes as well as Cu 2 O/CuO and p-Si(111) photocathodes by restraining the nonradiative recombination of their carrier. Our investigations ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…By contrast, the bare ZnO NWs with low MCD signals indicated that the minimal spin polarization in the bare ZnO NWs may lead to an indistinguishable magneto-PD effect. In addition, Yang et al, (2021) revealed that magnetic fields can weaken the nonradiative recombination of photoelectrodes’ carriers regardless of their ferromagnetic properties, contributing to improved photoelectrochemical reactions . However, the absence of a noticeable magneto-PD effect in the bare ZnO NWs herein indicated that the reported mechanism was inapplicable in our situation.…”
Section: Results and Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…By contrast, the bare ZnO NWs with low MCD signals indicated that the minimal spin polarization in the bare ZnO NWs may lead to an indistinguishable magneto-PD effect. In addition, Yang et al, (2021) revealed that magnetic fields can weaken the nonradiative recombination of photoelectrodes’ carriers regardless of their ferromagnetic properties, contributing to improved photoelectrochemical reactions . However, the absence of a noticeable magneto-PD effect in the bare ZnO NWs herein indicated that the reported mechanism was inapplicable in our situation.…”
Section: Results and Discussionmentioning
confidence: 67%
“…In addition, Yang et al, (2021) revealed that magnetic fields can weaken the nonradiative recombination of photoelectrodes' carriers regardless of their ferromagnetic properties, contributing to improved photoelectrochemical reactions. 31 However, the absence of a noticeable magneto-PD effect in the bare ZnO NWs herein indicated that the reported mechanism was inapplicable in our situation. Furthermore, for the surface photocatalytic reaction, the spin-polarized electrons had a considerable inhibitory effect on the recombination of active species (free radicals).…”
Section: Enhancement Of Spin Polarization Near the Fermi Level In Co ...mentioning
confidence: 56%
“…In addition, the coupling of photocatalysis with external fields (e.g., electric fields, thermal fields, magnetic fields, and ultrasonic radiation) is also worth considering, because it may produce synergistic effects that can potentially overcome the intrinsic low conversion rates of single photocatalytic process. [216][217][218] External fields can generate additional driving forces to promote the charge carrier transfer and separation, and consequently the photocatalytic efficiency. Reproduced with permission.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Consequently, the positive effect of magnetic field on separation and transfer characteristics of charge will lead to the reduction of photoelectrodes overpotential. [ 63 ]…”
Section: Fundamental Mechanismmentioning
confidence: 99%